Masculinities and Caring Professions. The Case Study of Students Enrolled in University Courses in Educational Disciplines - Masullo, Giuseppe; Coppola, Marianna (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The article examines the reasons behind young men’s choice to enrol in career-qualifying programmes for care-related professions (such as BA in Primary Education, Early Years Practitioner, Social pedagogy Practitioner) – a traditionally feminised area. The research points to three main motivations: (1) a forced choice, to accrue training credits in these courses and then enrol in a Psychology programme; (2) looking forward to the socialisation processes of educators; (3) personal aptitudes and inclinations towards this profession – or because they felt unsuited for other options and found other programmes unappealing, making it a choice by exclusion. The research aimed at understanding how students relate to the widespread male gender models, given that care and education professions require characteristics not positively associated with hegemonic masculinity. The research shows that the interviewees disapprove of certain traits associated with the hegemonic masculinity model, such as aggressiveness and inability to listen. However, they exhibit little reflexivity about the privileges linked to gender and fail to connect these with factors of oppression, especially when distancing themselves from subordinate or “homosexual” masculinities. This reflexivity, however, emerges among those who, due to their educational choices, have faced social stigmatisation, which compelled them to become more aware of the consequences of perpetuating gender roles and the resulting discrimination.